Conjugated Polymer Blends for Organic Thermoelectrics. (11th January 2019) - Zuo, Guangzheng; Abdalla, Hassan; Kemerink, Martijn
Abstract: A major attraction of organic conjugated semiconductors is that materials with new, emergent functionality can be designed and made by simple blending, as is extensively used in, e.g., bulk heterojunction organic solar cells. Herein doped blends based on organic semiconductors (OSCs) for thermoelectric applications are critically reviewed. Several experimental strategies to improve thermoelectric performance, measured in terms of power factor (PF) or figure‐of‐merit ZT, have been demonstrated in recent literature. Specifically, density‐of‐states design in blends of two OSCs can be used to obtain electronic Seebeck coefficients up to ≈2000 µV K −1 . Alternatively, blending with (high‐dielectric constant) insulating polymers can improve doping efficiency and thereby conductivity, as well as induce more favorable morphologies that improve conductivity while hardly affecting thermopower. In the PEDOT:polystyrene‐sulfonate (PEDOT:PSS) blend system, processing schemes to either improve conductivity via morphology or via (partial) removal of the electronically isolating PSS, or both, have been demonstrated. Although a range of experiments have at least quasi‐quantitatively been explained by analytical or numerical models, a comprehensive model for organic thermoelectrics is lacking so far. Abstract : Strategies to increase thermoelectric performance of doped organic semiconductors by blending are reviewed. Experimental results are, where possible, compared to analytical and numerical models. Several promising strategies to increase conductivity and/or thermopower are experimentally identified in recent literature. In contrast, formal understanding, especially of the role of morphology, is somewhat lagging behind.